A Kaldorian Perspective on the Turkish Economy (1980–2020) - Gülbahar Atasever (İstanbul İktisat Dergisi)
The most basic economic indicators used in international comparisons are inflation rate, unemployment rate, economic growth rate, and current account balance. In this context, when these variables are taken together within the framework of an index, they offer a practical perspective on a single country basis or in international comparisons. In this study, variables were analyzed using the TOPSIS method. During the 1980–2020 period, the narrow context of the aforementioned variables for the core, extended core, Keynesian, and heterodox Boratav year indices were calculated to make comparisons on the basis of time periods in the Turkish economy. The results obtained indicate that breakdowns in the indices by year are very similar; however, the indices differ considerably in interpreting periodic macroeconomic performance. Regarding the designated best period in terms of macroeconomic performance, while1980–1989 was the period in extended core and Keynesian indices, it was 1990–1999 according to the Boratav heterodox index, 2010–2020 according to the narrow core index, and 2000–2009 according to TOPSIS method. This result demonstrates that the Kaldorian perspective is insufficient for efficiency comparisons between periods, as factors such as human capital, productivity, institutions, and populations are excluded from the analysis.